2016
DOI: 10.24102/ijafr.v5i1.596
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Determinants of Vertical and Horizontal Integration among Smallholder Dairy Farmers in Lower Central Kenya

Abstract: Abstract.This study sought to analyze the determinants of vertical and horizontal integration among smallholder dairy farmers in Lower Central Kenya. Integration leads to high gross margins, influences choice of marketing channel and improves market participation, encouraging commercialization of dairy smallholder farming. A logit regression model was used to determine the likelihood of a household to integrate vertically or horizontally in its dairy enterprise. A multistage sampling technique was used, and da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
21
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 18 publications
6
21
1
Order By: Relevance
“…The possible reason that the longer the distance, the higher the production costs, hence the channel which is associated with higher production costs reduces farmer's gross margins. This research finding is consistent with the results of Mutura et al (2015).…”
Section: Lagged Onion Market Pricesupporting
confidence: 83%
See 1 more Smart Citation
“…The possible reason that the longer the distance, the higher the production costs, hence the channel which is associated with higher production costs reduces farmer's gross margins. This research finding is consistent with the results of Mutura et al (2015).…”
Section: Lagged Onion Market Pricesupporting
confidence: 83%
“…This implied that the probability of selling onions to assembler's market channel would be decrease than the probability of selling to retailer market channel choice. This result consistent with Bongiwe and Micah (2013), Mutura et al (2015), were found that education affect vegetable and diary market channel choice negatively, respectively.…”
Section: Distance To Nearest Urban Marketsupporting
confidence: 82%
“…Number of dairy cows had a positive and statistically significant (p = 0.000) relationship with the quantity of milk sold by households. Mutura, Nyairo, Mwangi, and Wambugu (2015) observed that increase in output per day increased probability of choice of cooperatives which take large volumes of milk as a way of lowering transaction cost by avoiding excess milk spoilage.…”
Section: Discussionmentioning
confidence: 99%
“…i  Previous studies highlight that farmers' milk market channel choice was affected by sales price, milk output, personal relationship, access to information, transaction cost and easements of payment (Mutura, Nyairo, Mwangi, & Wambugu, 2016;Tsourgiannis et al, 2008). Other factors affecting milk market channel choice include the distance to a collection center, education level, membership to farmers' groups, extension contact, number of dairy cows owned, and better milk price (Demissie et al, 2018;Kuma et al, 2013;Moturi, Obare, & Kahi, 2015).…”
Section: Eqmentioning
confidence: 99%